Tailoring deformation mechanisms in polycrystalline CoNi-base superalloys for enhanced high temperature strength. (15th March 2023) - Bezold, A.; Neumeier, S.
Abstract: The significance of segregation processes during high temperature deformation in superalloys has become increasingly evident in recent years. Here, the importance of additionally tailoring the active deformation mechanisms is shown by correlating the strain-rate dependent high temperature strength of two slightly different polycrystalline CoNi-base superalloys with their underlying defect structures. Transmission electron microscopy investigations revealed that at high strain-rates shearing by APB-coupled dislocation pairs occurs in both alloys. With decreasing strain-rate, the deformation mechanism in one alloy transitions to stacking fault shearing and at very low strain-rates also to microtwinning, while APB-based shearing remains dominant in the other alloy. In comparison, stacking fault shearing induced a relative increase in strength of 200 MPa, which is diminished to 100 MPa as microtwinning becomes more prevalent implying that the high temperature strength of this alloy system can be significantly increased by tailoring the acting deformation mechanism. Graphical abstract: Image, graphical abstract